Controlled Growth of CH3NH3PbI3 Using a Dynamically Dispensed Spin‐Coating Method: Improving Efficiency with a Reproducible PbI2 Blocking Layer. Issue 12 (24th May 2017) - Ma, Yingzhuang; Vashishtha, Parth; Chen, Kai; Peach, Elijah L.; Ohayon, David; Hodgkiss, Justin M.; Halpert, Jonathan E.
Abstract: It is commonly believed that excess PbI2 has beneficial effects for perovskite solar cells owing to the modification of charge‐transport behavior at interfaces, by surface passivation and by blocking electron‐hole recombination. Here, we introduce a dynamically dispensed spin‐coating technique in a two‐step deposition to form a perovskite layer with controllable quantities of crystalline PbI2 . Using this technique, the concentration of CH3 NH3 I solution is kept constant at the reaction interface, ensuring smooth growth of films. By changing the spinning rate during the reaction, the PbI2 conversion ratio and perovskite cuboid size can be optimized, resulting in a power conversion efficiency improvement over control devices. This dynamically dispensed technique represents a repeatable method for compositional control in perovskite solar cells and improves our understanding of how a PbI2 blocking layer improves the performance of perovskite solar cells. Abstract : Dynamic spinning : We introduce a dynamically dispensed spin‐coating technique in a two‐step deposition to form a perovskite layer with controllable quantities of crystalline PbI2 . Using this technique, the concentration of CH3 NH3 I solution is kept constant at the reaction interface, ensuring smooth growth of films for use in perovskite solar cells.